A photo- and electrochemically-active porphyrin–fullerene dyad electropolymer - Gervaldo, Miguel Andres (2010)
A hole- and electron-conducting polymer has been prepared by electropolymerization of aporphyrin–fullerene monomer. The porphyrin units are linked by aminophenyl groups to form a linear chain in which the porphyrin is an integral part of the polymer backbone. The absorption spectrum of a film formed on indium-tin-oxide-coated glass resembles that of a model porphyrin–fullerene dyad, but with significant peak broadening. The film demonstrates a first oxidation potential of 0.75 V vs. SCE, corresponding to oxidation of the porphyrin polymer, and a first reduction potential of -0.63 V vs. SCE, corresponding to fullerene reduction. Time-resolved fluorescence studies show that the porphyrin first excited singlet state is strongly quenched by photoinduced electron transfer to fullerene. Transient absorption investigations reveal that excitation generates mobile charge carriers that recombine by both geminate and nongeminate pathways over a large range of time scales. Similar studies on a related polymer that lacks the fullerene component show complex, laser-intensity-dependent photoinduced electron transfer behavior. The properties of the porphyrin–fullerene electropolymer suggest that it maybe useful in organic photovoltaic applications, wherein light absorption leads to charge separationwithin picoseconds in a “molecular heterojunction” with no requirement for exciton migration.